Clinical characteristics and dose-volume histogram parameters associated with the development of pleural effusions in non-small cell lung cancer patients treated with chemoradiation therapy. - Deek, Matthew P.; Nagarajan, Sairaman; Kim, Sinae; Ahmed, Inaya; Paul, Shiby; Scher, Eli D.; Listo, Matthew; Chen, Andrew; Aisner, Joseph; Hussain, Sabiha; Haffty, Bruce G.; Jabbour, Salma K. (Acta Oncologica, 2016)
Background:To investigate descriptive characteristics and dose metric (DM) parameters associated with development of pleural effusions (PlEf) in non-small cell lung cancer (NSCLC) treated with definitive chemoradiation therapy (CRT). Materials and methods:We retrospectively assessed treatment records and follow-up imaging of 66 NSCLC patients to identify PlEf formation after CRT. PlEf association between mean heart dose (MHD), mean lung dose (MLD), heart V5–V60(HV), and lung V5–V60(LV) were evaluated using Cox Proportional Hazard Models. Results:A total of 52% (34 of 66 patients) of our population developed PlEf and the actuarial rates at 6 months, 12 months, and 18 months were 7%, 30%, and 42%, respectively. Median time to diagnosis was five months (range 0.06–27 months). The majority of PlEfs were grade one (67%) and developed at a median of four (0.06–13) months, followed by grade two (15%) at a median 11 (5–12) months, and grade three (18%) at a median of 11 (3–27) months. On multivariate analysis, increasing HV5–HV50, LV5–LV50, MHD, and MLD were associated with greater risk of PlEf. Higher grade PlEf was also associated with higher doses of radiation to the heart, while lung DM parameters were not significantly associated with higher PlEf grades. At five-months post-CRT, MHD of 25 Gy was associated with a 100% chance of grade one PlEf, an 82% risk of grade two PlEf, and a 19% risk of grade three PlEf. Conclusions:Post-CRT PlEf is common in NSCLC with the majority being grade one. Increasing heart and lung irradiation was associated with increased risk of PlEf. Increasing heart irradiation also correlated with development of increasing grades of PlEf. The impact of potential cardiopulmonary toxicity and resultant PlEfs after CRT requires additional study.